The sensitivity of algae to the effect of antifungal drugs - Tulegenova, S.E.; Beisenova, R.R.; Auelbekova, A.K. (KSU publ., 2020)
The presence of pharmaceuticals, their metabolites and transformation products in the aquatic environment has become an increasingly serious problem in recent decades. Currently, people are using various pharmaceuticals. However, after their use, the drugs are removed to the wastewater treatment plant, where they cannot be completely eliminated. As a result, they reach the surface of the water. Their discovery in the environment and their biological activity raise concerns about potential adverse effects on non-target species. In this study, two of the most widely used pharmaceuticals in Kazakhstan, namely ketoconazole and terbinafine, were tested for water toxicity using Chlorella species. These drugs were selected because they are one of the priority drugs based on risks for aquatic biota in Kazakhstan. The study assessed the effects of antifungal drugs for 72 hours by cell count, cell growth rate of Chlorella sp. We investigated the effects of substances in concentrations of 20–100 mg/L. As a result of the study, eco-absolute objects, compared with the control group, had a significant effect on the growth of Chlorella sp. cells, which led to 97.7±0.004 % (ketoconazole) and 96.19±0.007 % (terbinafine) inhibition of growth. In addition, the results showed that the growth rate of the representative of the aquatic biota Chlorella sp. decreased four times. This proves that Chlorella sp. are vulnerable to exposure to pharmaceuticals.
Keywords: environment; pollutants, quantification; ketoconazole; terbinafine; antifungal drugs; Chlorella sp.; growth rate; growth inhibition; growth medium Tamiya